2011
DOI: 10.1111/j.1467-9922.2011.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Raters From India to Score a Large‐Scale Speaking Test

Abstract: We investigated the scoring of the Speaking section of the Test of English as a Foreign Language TM Internet-based (TOEFL iBT R ) test by speakers of English and one or more Indian languages. We explored the extent to which raters from India, after being trained and certified, were able to score the TOEFL examinees with mixed first languages accurately and consistently. The effectiveness of a special training package designed for scoring Indian examinees was examined as well. We found that the raters from Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 27 publications
8
46
1
Order By: Relevance
“…The substantial rater severity/leniency differences among raters, as was also found in some previous research (e.g., Attali, 2016;Bijani & Fahim, 2011;Xi & Mollaun, 2011), have important consequences for decision makers, in that in rater training more attention and importance should be dedicated to withinrater consistency (intra-rater agreement) than to between-rater consistency (interrater agreement).…”
Section: Discussionsupporting
confidence: 57%
“…The substantial rater severity/leniency differences among raters, as was also found in some previous research (e.g., Attali, 2016;Bijani & Fahim, 2011;Xi & Mollaun, 2011), have important consequences for decision makers, in that in rater training more attention and importance should be dedicated to withinrater consistency (intra-rater agreement) than to between-rater consistency (interrater agreement).…”
Section: Discussionsupporting
confidence: 57%
“…Zhang and Elder (2011) compared Chinese native speakers and English native speakers' ratings of Chinese students' oral proficiency in the national College English Test-Spoken English Test (CET-SET) in China. More recently, however, researchers have become more interested in speakers of English varieties from Outer Circle countries such as India (Carey et al, 2011;Hsu, 2012;Xi & Mollaun, 2011). Xi and Mollaun (2011) investigated to what extent certified and trained TOEFL iBT Speaking Test raters from India could rate as consistently and reliably as operational raters from the United States and what effects a special training package, in which raters were only exposed to Indian test takers' responses, had on raters' scores and rater confidence.…”
Section: Introductionmentioning
confidence: 99%
“…Groups of phonetically trained judges and untrained raters display great agreement in their overall ratings (e.g. Bongaerts et al, 1997;Hopp & Schmid, 2013), even though interrater reliability was found to be higher among trained raters in some studies (Thompson, 1991, though see Xi & Mollaun, 2011).…”
Section: Ratersmentioning
confidence: 99%
“…Other studies on holistic oral production assessment find that rater familiarity with the particular language combinations in the speakers affects ratings among raters who are native (e.g. Carey, Mannell & Dunn, 2011;Winke, Gass & Myford, 2012) as well as non-native (Xi & Mollaun, 2011, Zhang & Elder, 2011 speakers of the language to be rated. In addition, several studies report that familiarity with regional accents and dialects that may occur in the speech samples affects ratings of foreign accent (e.g.…”
Section: Ratersmentioning
confidence: 99%